1980
DOI: 10.1210/endo-107-2-626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclic Nucleotides on Deoxyribonucleic Acid Synthesis in Hypophysectomized Rat Cartilage: Stimulation of Thymidine Incorporation and Potentiation of the Action of Somatomedin by Analogs of Adenosine 3′,5′-Monophosphate or a Cyclic Nucleotide Phosphodiesterase Inhibitor*

Abstract: The actions of cyclic nucleotides on basal and somatomedin-stimulated thymidine incorporation into DNA by costal cartilage from hypophysectomized rats were investigated. Three analogs of cAMP (dibutyryl, 8-bromo, and 8-dimethylamino derivatives, which are alternate activators of cAMP-dependent protein kinase and resistant to degradation by cAMP phosphodiesterase but represent a wide difference in potency as phosphodiesterase inhibitors) in range of concentrations from about 10(-5) to 3 X 10(-4) M enhanced basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1982
1982
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Specificity of growth factor stimulation of chondrocyte colony formation Previous studies have shown that in addition to FGF, other agents, including EGF, insulin, IGF, and dibutyryl cyclic-AMP, stimulate the growth of chondrocytes in monolayer and organ cultures (Bomboy and Salmon, 1980;Prins et al, 1982;Kato et al, 1983). Table 1 shows the effect of these and other mitogens on growth in soft agar of chick embryo chondrocytes.…”
Section: Effect Of Increasing Concentrations Of Fgf On Colonymentioning
confidence: 99%
“…Specificity of growth factor stimulation of chondrocyte colony formation Previous studies have shown that in addition to FGF, other agents, including EGF, insulin, IGF, and dibutyryl cyclic-AMP, stimulate the growth of chondrocytes in monolayer and organ cultures (Bomboy and Salmon, 1980;Prins et al, 1982;Kato et al, 1983). Table 1 shows the effect of these and other mitogens on growth in soft agar of chick embryo chondrocytes.…”
Section: Effect Of Increasing Concentrations Of Fgf On Colonymentioning
confidence: 99%
“…This finding indicates that PTH stimulation of chondrocyte phenotypic expression is not linked to its growth stimulation, and that the mitogenic action of PTH is not mediated by cAMP. The effects of cAMP analogue mimicked those of PTH in chondrocytes (5,8,9,29,30), but dibutyryl cAMP enhanced chondrocyte growth (8,9,30) (32). Furthermore, PTH is found in fetal blood of various animals, and its level (10-'1-10-'0 M) is similar to the maternal level (monkey [33]; miniature pig [34]; rabbit [Kato, Y., and T. Koike, unpublished observations]).…”
Section: Introductionmentioning
confidence: 98%
“…These findings suggest that with respect to cyclic AMP metabolism, the re¬ sponse of chondrocytes to MSA differs from that of fibroblasts. Recently, Bomboy & Salmon (1980) showed that analogues of cyclic AMP and cyclic nucleotide phosphodiesterase inhibitor markedly potentiate the effect of somatomedin on DNA synthesis in cultured cartilage from hypophysectomized rats. Analogues of cyclic AMP stimulate DNA synthesis in chondrocytes in organ culture (Bomboy & Sal¬ mon 1980), but they suppress DNA synthesis in monolayer cultures (Miller et al 1979;Takigawa et al 1981).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that the de¬ crease in cyclic AMP level may be related to the action of somatomedin on macromolecule synthe¬ sis. Cyclic AMP analogues have been shown to be potent stimulators of proteoglycan synthesis (Miller et al 1979;Takigawa et al 1981), RNA synthesis (Drezner & Uebovitz 1979) and DNA synthesis (Bomboy & Salmon 1980) in chondrocytes. Taki¬ gawa et al (1981) showed that parathyroid hor¬ mone (PTH) increases ornithine decarboxylase activity and proteoglycan through increase of cyclic AMP.…”
mentioning
confidence: 99%